Perkembangan Sosial pada Anak Sekolah Dasar - Kurniawan, Eka Yulyawan; Cendany, Nafisa Nuarista; Rosadah, Rosadah (TSAQOFAH, 2024)
The most important developmental aspect in determining student success is social development. In fact, currently some elementary schools still do not understand the pattern of development of their students (Anisah & Hakam, 2022). In line with the previous statement, Syukri (2021) argues that teachers do not really understand the solution to overcome the shortcomings of their students. This is also felt in SDN Duri Kosambi 06 Pagi, teachers have not been able to understand the pattern of social development in children so that it hampers the learning process. This research use desciptive qualitative approach. The population of this study were all students of SDN Duri Kosambi 06 Pagi. From the total population, researchers took samples using purposive sampling technique. The sample in this study were 30 students in class V. Based on observations, this is proven by the existence of several social problems for children, including (1) students are still reluctant to participate in group work activities; (2) students still often choose friends; (3) there are still students who are excluded; (4) students only want to work in groups with close friends; (5) students have not been able to express and share feelings with their peers; (6) students have not been able to take responsibility for their obligations; and so forth. The low social aspect needs attention from all parties.